038 Drug eluting stent implantation is associated with lower mace rates than bare metal stent implantation in primary PCI for ST elevation myocardial infarction. (16th May 2012) - Bromage, D I; Rathod, K S; Jones, D A; Jain, A; Knight, C; Mathur, A; Wragg, A
Abstract : Introduction: Drug-eluting stent (DES) implantation during the treatment of ST-elevation myocardial infarction (STEMI) by primary percutaneous coronary intervention (PCI) is controversial due to concerns regarding increased risk of stent thrombosis. We therefore studied long-term outcomes after DES vs bare metal stent (BMS) implantation during primary PCI. Methods: Between October 2003 and September 2010, 2170 consecutive patients undergoing primary PCI for STEMI at a single high-volume London centre were included. The primary end point was major adverse cardiac events (MACE), defined as death, myocardial infarction (MI), stroke and target vessel revascularisation (TVR). Median follow-up was 2 years (IQR 0.7–3.6 years). Results: 442 patients underwent PCI with DES and 1728 with BMS. Differences in baseline characteristics are outlined in Abstract 038 table 1 . There was a significant difference in MACE between the groups in favour of DES (3.9% vs 7.7%, p=0.006) (Abstract 038 figure 1 ). Age-adjusted Cox analysis demonstrated the decrease in MACE in patients undergoing DES compared to BMS implantation was maintained with multiple adjustment (HR 0.60 [95% CI 0.37 to 0.96]). In addition, after regression adjustment incorporating a propensity score (age, stent length, stent width, gender, ethnicity, previous MI, PCI or coronary artery bypass grafting (CABG), diabetes, hypertension, hypercholesterolaemia, smoking status, presence or absence of shock, and ejection fraction) into the hazards model as a covariate, this difference persisted (HR 0.61 [95% CI 0.37 to 0.96]). Conclusion: DES implantation is associated with lower MACE rates than BMS implantation in primary PCI for STEMI.